Associations between eating disorder related symptoms and participants' utilization of an individualized Internet‐based prevention and early intervention program. Issue 10 (18th September 2017) - Kindermann, Sally; Moessner, Markus; Ozer, Fikret; Bauer, Stephanie
Abstract: Objective: Flexible, individualized interventions allow participants to adjust the intensity of support to their current needs. Between‐persons, participants with greater needs can receive more intense support, within‐persons, participants can adjust utilization to their current level of symptoms. The purpose of the present study was to analyze associations between ED‐related symptoms and utilization of the individualized program ProYouth both between‐ and within‐persons, aiming to investigate whether participants adapt utilization intensity to their current needs. Method: Generalized estimated equations (GEEs) were used to analyze log data on program utilization (monthly page visits, monthly use of chats and forum) assessed via server logs and self‐reported data on ED‐related symptoms from N  = 394 ProYouth participants who provided longitudinal data for at least two months. Results: Between‐persons, page visits per month were significantly associated with compensatory behavior, body dissatisfaction, and binge eating. Monthly use of the more intense modules with personal support chat and forum was associated with the frequency of compensatory behavior. Within‐persons, unbalanced nutrition and dieting showed the strongest associations with monthly page visits. Monthly use of chats and forum was significantly associated with compensatory behavior and unbalanced nutrition and dieting. Discussion: Results indicate that program utilization is associated with ED‐related symptoms between‐ as well as within‐persons. The individualized, flexible approach of ProYouth thus seems to be a promising way for Internet‐based provision of combined prevention and early intervention programs addressing ED.